2023
DOI: 10.3390/su15053977
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Land Use in the Beijing–Tianjin–Hebei Region of China Based on the GMOP-PLUS Coupling Model

Abstract: The changeable patterns and contractions of land use have become increasingly significant in recent years as the economy and society have rapidly developed. Subsequently, land use change simulation has become a focal point in the study of land use patterns and change processes. Four development scenarios in 2030, including business-as-usual, ecological protection, economic development, and sustainable development scenarios, are proposed to realize the sustainable development of land use in Beijing–Tianjin–Hebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Some studies have incorporated residents' happiness, environmental satisfaction, and other factors into the objective functions of regional resource optimization, but these indicators are difficult to quantify. We also compared the results of this study with other studies on land use optimization in the Beijing-Tianjin-Hebei region (Bao et al, 2021;Meng et al, 2023), where the land use change trends showed spatial consistency under the same context, and the scale of the transformation of land classes into each other was roughly the same, but due to the differences in benefit coefficients selection, the economic value of the optimized and the ecosystem service values may be measured differently due to differences in the selection of benefit coefficients. However, compared with the traditional multi-objective optimization, this study based on nutritional goals and taking into account other development scenarios, achieving a combination of micro and macro levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have incorporated residents' happiness, environmental satisfaction, and other factors into the objective functions of regional resource optimization, but these indicators are difficult to quantify. We also compared the results of this study with other studies on land use optimization in the Beijing-Tianjin-Hebei region (Bao et al, 2021;Meng et al, 2023), where the land use change trends showed spatial consistency under the same context, and the scale of the transformation of land classes into each other was roughly the same, but due to the differences in benefit coefficients selection, the economic value of the optimized and the ecosystem service values may be measured differently due to differences in the selection of benefit coefficients. However, compared with the traditional multi-objective optimization, this study based on nutritional goals and taking into account other development scenarios, achieving a combination of micro and macro levels.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the applications of multi-objective optimization techniques in sustainable and resilient urban planning, addressing crucial objectives, such as compactness, flood impact mitigation, carbon emission reduction, economic benefits, and sustainable development [22][23][24][25][26]. The utilization of various optimization methods reflects the interdisciplinary nature of the field and the diverse approaches employed to tackle complex urban planning challenges.…”
Section: Applications Of Multi-objective Optimization In Urban Planningmentioning
confidence: 99%
“…The PLUS model consists of the land expansion analysis strategy (LEAS) and the CA model based on multi-type random patch seeds (CARS) [35]. In this study, fourteen natural and social factors (Table 2) were selected as driving factors of land use change according to previous studies and the availability of data [36][37][38]. Combined with the dynamic driving factors (GDP, population, precipitation, and temperature) under the SSP-RCP scenario, the land use under the SSP-RCP scenario was simulated using the PLUS model.…”
Section: Plus Modelmentioning
confidence: 99%